2020
DOI: 10.1200/go.20.00316
|View full text |Cite
|
Sign up to set email alerts
|

Survival Differences in Chinese Versus White Women With Breast Cancer in the United States: A SEER-Based Analysis

Abstract: PURPOSE The affect of race on breast cancer prognosis is not well understood. We compared crude and adjusted breast cancer survival rates of Chinese women versus White women in the United States. METHODS We conducted a cohort study of Chinese and White women with breast cancer diagnosed between 2004 to 2015 in the SEER 18 registries database. We abstracted information on age at diagnosis, tumor size, grade, lymph node status, receptor status, surgical treatment, receipt of radiotherapy and chemotherapy, and de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 27 publications
(25 reference statements)
1
19
3
Order By: Relevance
“…In the present study, the race was not the predictor associated with high RS. In addition, our study showed similar BCSS between Chinese and WA BC, which was contrary to the results from the previous SEER studies [10,11]. Therefore, differences in demographic and tumor features between Chinese and WA BC may contribute to the disparity between our study and the previous SEER studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In the present study, the race was not the predictor associated with high RS. In addition, our study showed similar BCSS between Chinese and WA BC, which was contrary to the results from the previous SEER studies [10,11]. Therefore, differences in demographic and tumor features between Chinese and WA BC may contribute to the disparity between our study and the previous SEER studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Two previous SEER studies have shown that Chinese women in the US have better BCSS compared to WA women [10,11]. However, in our study, we did not found that Chinese BC patients had lower risks of breast cancer-specific mortality than WA patients.…”
Section: Discussioncontrasting
confidence: 97%
See 1 more Smart Citation
“…In cases wherein clinicopathological characteristics are different among studies, a random-effects model results could be more appropriate than a fixed-effects model. Lim et al have reported that the clinicopathological staging and survival outcomes are different between Asian and European groups [ 52 ]. Therefore, a random-effects model results would be more recommended in the subgroup analysis according to the study area.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the differences of dietary habits, regarding the flavonoid consumption tendencies among populations can be suggested as a factor for this phenomenon. Furthermore, the breast cancer prevalence increase, among Asian women who migrate to western countries, may also be considered as evidence for the protective effect of flavonoids against breast cancer (6).…”
Section: Introductionmentioning
confidence: 99%